TRAINER IN CREATING MULTIMEDIA LEARNING USING ISPRING PRESENTER FOR PPG DALJAB 2 STUDENTS - Suryani, Karmila (Jurnal PADAMU NEGERI (Pengabdian pada Masyarakat Bidang Eksakta), 2024)
The Community Service Activity (PKM) aims to provide training to students of the In-service Teacher Professional Education Program (PPG Daljab) Batch 2 regarding training in making learning multimedia using the Ispring Presenter application. The method for implementing PKM is through training which consists of three stages, namely the preparation stage, implementation stage and evaluation stage. The preparation stage carried out a survey of the needs of PPG Daljab Batch 2 students regarding learning media, the implementation stage was conducting multimedia development training, while the evaluation stage was carried out by giving satisfaction questionnaires with the implementation of the training to all participants. The research instrument used a questionnaire with data analysis in the form of percentage of satisfaction with training. The results obtained were that the training participants were very satisfied with the training activities in terms of event preparation, materials and training activities